Spatial and Temporal Ecological Uniqueness of Andean Diatom Communities Are Correlated With Climate, Geodiversity and Long-Term Limnological Change - Benito, Xavier; Vilmi, Annika; Luethje, Melina; Carrevedo, Maria Laura; Lindholm, Marja; Fritz, Sherilyn C. (Frontiers in Ecology and Evolution, 2020)
High-elevation tropical lakes are excellent sentinels of global change impacts, such as climate warming, land-use change, and atmospheric deposition. These effects are often correlated with temporal and spatial beta diversity patterns, with some local communities contributing more than others, a phenomenon known as local contribution to beta diversity (LCBD) or ecological uniqueness. Microorganisms, such as diatoms, are considered whole-ecosystem indicators but little is known about their sensitivity and specificity in beta diversity studies, mostly because of the lack of large spatial and temporal datasets. To fill this gap, we used a tropical South American diatom database comprising modern (144 lakes) and paleolimnological (6 sediment cores) observations to quantify drivers of spatial and temporal beta diversity and evaluate implications for environmental change and regional biodiversity. We used methods of beta diversity partitioning (replacement and richness components) by determining contributions of local sites to these components (LCBDrepl and LCBDrich), and studied how they are related to environmental, geological, and historical variables using Generalized Additive Models. Beta replacement time series were also analyzed with GAM to test whether there is widespread biotic homogenization across the tropical Andes. Modern lake ecological uniqueness was jointly explained by limnological (pH), climatic (mean annual precipitation), and historical human impacts. Limnological (conductivity) and geodiversity variables (terrain ruggedness, soil variability) were inversely correlated to replacement and richness components of local contribution to beta diversity, suggesting that not all lakes contributing to regional diversity are targets for conservation actions. Over millennial time scales, decomposing temporal trends of beta diversity components showed different trajectories of lake diatom diversity as response of environmental change. This is shown by i) increased hydroclimatic variability (as inferred by decreased temperature seasonality) mediating higher contribution of richness to local beta diversity patterns ca. 1000 years ago in Ecuador Andean lakes; and ii) lake-specific temporal beta diversity trends for the last ca. 200 years, indicating that biotic homogenization is not widespread across the tropical Andes. Our approach for unifying diatom ecology, metacommunity studies, and paleolimnology can facilitate the understanding of future responses of tropical Andean lakes to global change impacts.